Evaluation of Stentangioplasty in University Cardiac Center - Rahman, F; Banerjee, S; Ahmed, CM; Jamil, AA; Uddin, MS; Alam, S; Bhattchrjo, B; Azam, G; Sarker, H; Shamim, K; Rashid, H; Diva, F; et al. (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 197-203The abstract of this article is available on the PubMed website